2002
DOI: 10.1590/s0034-89102002000700001
|View full text |Cite
|
Sign up to set email alerts
|

Consumo infantil de alimentos industrializados e renda familiar na cidade de São Paulo

Abstract: Resumo ObjetivoDescrever o consumo infantil de alimentos industrializados e a relação com a renda familiar per capita, com base em inquérito domiciliar. Métodos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
44

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 5 publications
1
17
0
44
Order By: Relevance
“…3,4,14 In the present study, these nutrients showed the highest proportions of non-compliance of samples.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…3,4,14 In the present study, these nutrients showed the highest proportions of non-compliance of samples.…”
Section: Discussionsupporting
confidence: 47%
“…4,e These products were purchased in the city of São Paulo, Southeastern Brazil, between 2001 and 2005. Samples were gathered using the Health Surveillance Agency standard inspection procedure, in accordance with the current legislation, f and subsequently sent to the Instituto Adolfo Lutz (Adolfo Lutz Institute) for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Nas creches do município onde se realizou este estudo não havia uma programação de ações preventivas junto aos escolares dessa faixa etária ou atendimento odontológico de rotina. Confirmando dados de literatura [49][50][51][52] houve uma porcentagem mais alta de cárie severa nos extratos socioeconômicos mais baixos, com uma maior concentração de crianças com ceo-d maior que 5 nos níveis E-F. Coerentemente, 67,57% crianças que frequentavam escolas particulares estavam livres de cárie, não foi encontrada nenhuma ocorrência de ceo-d maior ou igual a cinco, enquanto que das crianças matriculadas nas CEI's municipais, 45,76% estavam livres de cárie e 20,82% tinham ceo-d maior ou igual a cinco. Para Pauleto et al 46 , a saúde bucal e o de- 53 .…”
Section: Discussionunclassified
“…The introduction of energy-dense foods with low nutritional value from the beginning of life and the early withdrawal of breastfeeding contribute to impaired growth and development, and lead to decreased immune protection, triggering of allergic processes, and nutritional disorders 18 , 10 , 18 , 19 …”
Section: Discussionmentioning
confidence: 99%